Ketimpangan Distribusi Pendapatan di Kabupaten Banyumas Jawa Tengah - Pramono Hariadi; Arintoko Arintoko; Icuk Rangga Bawono (Economic Journal of Emerging Markets, 2008)
The central theme of this paper is the measurement of income inequality by investigating its present time in Banyumas. It is important to know the impact of local development process on income inequality. Not only the impacts of local development, but also other factors determining the trend of income inquality (i.e.fuel price raises, price and income adjustment policies) give impact on present income inequality. Nowaydays, the local development policies and the other factors are predicted that they give impact on the raise of recent income inquality in Banyumas. Based on Gini coefficient measurement method, we obtain startling result. The result presented in this paper is based on a sample of 180 households including urban area, sub urban area and rural area. The Gini coefficient result is 0,603. This result shows the sharp raise of income inequality from past time to recent in Banyumas. The imbalance of development between modern sectors (i.e services, contruction, finance, trade and manufacture) and traditional sectors (i.e agriculture and informal sector) causes the raise of income inequality. Based on this trend of the raise of income inequality, local government must practice pro poor development policies without ignoring sustainable economic growth and especially focusing on agriculture, rural economy, informal sector, small and medium industries. Keywords: income inequality, Gini coefficient, pro-poor policy, sustainable growth